Pencalonan Walikota dan Wakil Walikota oleh Partai Politik di Kota Semaranag Tahun 2015 - Mahardhika, Amanda Dewi (Unnes Political Science Journal, 2018)
The purpose of this research is to describe: 1) the nomination of the Mayor and Vice Mayor by the Partai Demokrasi Indonesia Perjuangan and the Partai Kebangkitan Nasional in Semarang by 2015 and 2) differenciation in the nomination of the Mayor and Vice Mayor by the Partai Demokrasi Perjuangan Indonesia and the Partai Kebangkitan Nasional in Semarang by 2015 The research approach is Qualitative. The research focus on: 1) the nomination of the Mayor and Vice Mayor by the Partai Demokrasi Indonesia Perjuangan and the Partai Kebangkitan Nasional in Semarang by 2015 and 2) differenciation in the nomination of the Mayor and Vice Mayor by the Partai Demokrasi Perjuangan Indonesia and the Partai Kebangkitan Nasional in Semarang by 2015. Data is obtained through interviews, documentation, and library studies. Triangulation technique is used as the data validity. Interactive model is used as data analysis. The results of this research are: 1) the nomination of a mayor and a vice Mayor in Semarang by PDI-P has been conducted in accordance with the rules of the PDI-P party number 4 year 2015 about the Recruitment and selection of Head Regional and Deputy Regional candidates of PDI-P from article 10 to article 19. In addition, the recruitment process is divided into 3 main stages thats are networking, screening and the determination of the candidates. In the PKB party candidacy of Mayor and Deputy Mayor have been adapted to the provisions of the party and the AD/ART party’s into six stages that’s are; preparation phase with the formation of the collecting and screening team, the stage of registration, verification, interview, selection, and the determination of the candidates. 2) differenciation of candidacy of the Mayor and Deputy Mayor in Semarang by PDI-P and PKB is based on five things.